Curcumin ameliorates oxidized low-density lipoprotein (ox-LDL)-caused damage in human umbilical vein endothelial cells (HUVECs) through the miR-599/MYD88/NF-κB axis. (December 2022) - Chen, Decai; Zhu, Chongmei; Ye, Shouwan; Yang, Qiong
Abstract: Background: The role of curcumin in multiple human diseases was widely reported, including arteriosclerosis (AS). We aimed to investigate the correlation between curcumin and AS-related microRNAs (miRNAs) to find out more underlying mechanism of curcumin used in AS. Methods: Cell proliferation and apoptosis were determined using CCK-8 assay, EdU staining assay, flow cytometry, and western blot for the detection of PCNA and Bax protein expression in human umbilical vein endothelial cells (HUVECs). Inflammation response was evaluated using ELISA kits, and oxidative stress was evaluated by detecting SOD activity and MDA level using the matched commercial kits. RT-qPCR analysis was applied for miR-599 and MYD88 mRNA level measurement. Results: Curcumin treatment and miR-599 overexpression could promote cell proliferation, and inhibit cell apoptosis, inflammation response and oxidative stress, thereby alleviating ox-LDL-induced cell damage in HUVECs. Mir-599 was lowly expressed and MYD88 was highly expressed in AS patients and AS cell model. Curcumin could modulate miR-599 to exert the protective effect on ox-LDL-caused cell damage, and miR-599 directly targeted MYD88 to alleviate ox-LDL-caused cell damage in HUVECs. Curcumin targeted miR-599 to regulate MYD88 expression, thereby inactivating the NF-κB pathway in AS cell model. Conclusion: Our findings illustrated that curcumin exhibited anti-AS effect through the miR-599/MYD88 axis and thereby inhibiting the NF-κB pathway. Highlights: MiR-599 was lowly expressed in atherosclerosis patients and ox-LDL-induced HUVECs. Curcumin and miR-599 overexpression could protect against ox-LDL-caused cell injury in HUVECs. Curcumin targeted miR-599 to alleviate ox-LDL-caused cell injury in HUVECs. MiR-599 bound to MYD88 to inactivate the NF-κB pathway in HUVECs.